The Analysis of Problems and Alternatives in Teaching and Learning Science in SMPN 1 Soe During The Covid -19 Pandemic - Agsen Hosanty Susana Billik (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2023)
Pandemic Covid-19 had a significant impact on the education sector, requiring learning is done online. This causes the science learning process in junior high school Negeri 1 Soe, changing the face-to-face learning system to online learning with using WhatsApp as a science learning medium. This study aims to analyze constraints and alternatives in the science learning process at SMP Negeri 1 Soe during the Covid-19 Includes 3 main components, namely planning, implementation and evaluation of learning. This research carried out on 16 students and 1 teacher of science subjects using the approach qualitative descriptive. Data collection techniques used are questionnaires, interviews and documentation. While the data analysis technique used is the Miles and Huberman model data analysis through 3 stages, namely data reduction, data display and drawing conclusions. The results of this study shows that students experience obstacles and difficulties such as, students do not have laptops, smartphone, inadequate internet network, minimal internet quota and difficulty doing the science practicum method. Based on these obstacles, the teacher provide an alternative for distributing student books containing materials and homework students according to the time and schedule of science lessons. This is done to overcome several obstacles and reduce the burden on students during the online science learning process during the Covid-19 pandemic.